Revising the legislation of Ethics Committees to ease biomedical research in humans across the world: lessons from the COVID-19 emergency: Ethics Committee legislation revision - Vinceti, Silvio Roberto; Filippini, Tommaso (Acta Biomedica Atenei Parmensis, 2022)
As a legislative domain that considerably influences implementation of biomedical research, the need to improve the legal rules surrounding the organization and functioning of Ethics Committees in public health, toxicology, and clinical medicine is widely recognized within and outside the European Union. Given the often-heard complaints by researchers about the complexity and length of both the application and the review process by Ethics Committees in the authorization of new studies, adjustments to their legislation appears to be warranted. Within the European Union this seems also all the timelier, given the upcoming new regulation of clinical trials to become effective in early 2022. For this process, valuable lessons can be gleaned from the COVID-19 pandemic and the changes in the functioning of Ethics Committees that were adopted to cope with the exceptional circumstances imposed by the health emergency. The pandemic experience clearly indicates that a more responsive and practical system of applications’ review by the Ethics Committees can be squared with acceptable levels of transparency and reliability in ethical accountability. For this reason, countries like Italy should consider undertaking a significant revision of the public law rules that govern the review processes of Ethics Committees in light of the pandemic experience. (www.actabiomedica.it)